Dampak Lingkungan Sekolah terhadap Hasil Belajar dan Kesehatan Mental Siswa - Agnes Angi Dian Winei; Ekowati Ekowati; Asep Setiawan; Jenuri Jenuri; Pius Weraman; Rosa Zulfikhar (Journal on Education, 2023)
This study aims to explore the impact of school environment on students' academic achievement and mental health through a literature review approach. The study analyzes the factors that influence the school environment, including physical, social, and academic environment, and how these factors can affect students' academic achievement and mental health. By collecting data from various literature studies, this study shows that a good school environment can have a positive impact on students' academic achievement and mental health. A comfortable and safe physical environment, a positive and inclusive social environment, and an academic environment that supports and motivates students can improve students' academic achievement and mental health. The practical implication of this study is that improving the school environment should be a priority to enhance the quality of education and student well-being.